Stoichiometric homeostasis of N:P ratio drives species-specific symbiotic N fixation inhibition under N addition - Li, Qiang; Philp, Joshua; Denton, Matthew D.; Huang, Yingxin; Wei, Jian; Sun, Huijuan; Li, Yang; Zhao, Qian (Frontiers in Plant Science, 2023)
Symbiotic N fixation inhibition induced by N supply to legumes is potentially regulated by the relative N and P availability in soil. However, the specific responses of different legume species to changes in N:P availability remain unclear, and must be better understood to optimize symbiotic N fixation inputs under N enrichment. This study investigated mechanisms by which soil N and P supply influence the symbiotic N fixation of eight legume species, to quantify the inter-specific differences, and to demonstrate how these differences can be determined by the stoichiometric homeostasis in N:P ratios (HN:P). Eight herbaceous legume species were grown separately in outdoor pots and treated with either no fertilizer (control), N fertilizer (14 g N m-2), P fertilizer (3.5 g P m-2) or both N and P fertilizer. Plant nutrients, stoichiometric characteristics, root biomass, non-structural carbohydrates (NSC), rhizosphere chemistry, P mobilization, root nodulation and symbiotic N fixation were measured. N addition enhanced rhizosphere P mobilization but drove a loss of root biomass and root NSC via exudation of P mobilization compound (organic acid), especially so in treatments without P addition. N addition also induced a 2-14% or 14-36% decline in symbiotic N fixation per plant biomass by legumes in treatments with or without P addition, as a result of decreasing root biomass and root NSC. The changes in symbiotic N fixation were positively correlated with stoichiometric homeostasis of N:P ratios in intact plants without root nodules, regardless of P additions. This study indicates that N addition can induce relative P limitations for growth, which can stimulate rhizosphere P mobilization at the expense of root biomass and carbohydrate concentrations, reducing symbiotic N fixation in legumes. Legume species that had less changes in plant N:P ratio, such as Lespedeza daurica and Medicago varia aintained symbiotic N fixation to a greater extent under N addition.